Hybrid IT and Multi Cloud an Emerging Trend and Improved Performance in Cloud Computing - Gundu, Srinivasa Rao; Panem, Charan Arur; Thimmapuram, Anuradha (SN computer science, 2020)
In the present day scenario cloud computing is an attractive subject for IT and non IT personnel. It is a service-oriented pay per use computational model. Cloud has working models with service-oriented delivery mechanism as well as deployment-oriented infrastructure mechanism. Data centers are the backbone of cloud computing. The massive participation of public has also increased the load on the cloud servers. Proper scheduling of resources is always needed. Quality of service is to be provided as per the service level agreement. Virtualization technique is the main reason behind the huge success of cloud. Multi-cloud exchanges to optimize connectivity today, multi-cloud exchanges offer the next level in direct connectivity, allowing organizations to safely and easily expand multi-cloud capabilities. Exchanges eliminate the added worries that an open Internet can bring as well as the tedious provisioning and configuring that comes with connecting to the public Internet. Importantly, multi-cloud exchanges allow organizations to establish a single connection to multiple cloud providers at the same time through an Ethernet switching platform, rather than wrestling with multiple individual connections to cloud providers.